Design of a novel dynamic trust model for spectrum management in WRANs of TV white space. (15th December 2017) - Wang, Cong; Ma, Maode; Zhao, Zenghua
Abstract: The cognitive radio (CR) technique is considered as a better and more efficient answer to the predicament brought by the high demands of wireless communication services and the scarcity or low utilization of frequency spectrum resources. The IEEE 802.22 standard has regulated the wireless regional area networks (WRANs) as one example of the CR networks, which is operating in the television white space (TVWS) spectrum. In the centralized WRANs, the secondary user base station (SUBS) allocates the spectrum holes for the customer premise equipment (CPE) on the basis of the spectrum sensing information from the CPEs around. However, since the CPEs are easy compromised under the varying and uncontrollable environment, the WRANs is subjected to the primary user emulation attacks (PUEA) and the spectrum sensing data falsification (SSDF) attacks, which may lead to a wrong global spectrum decision made by SUBS. A novel dynamic trust model for the SUBS spectrum management based on the subjective logic for the centralized WRANs of TVWS is proposed in this paper. The proposed trust model has a positive impact on reducing the influence of users' vicious behaviors and encourages the CPEs to participate in truthful actions for communications. The analysis shows that the time complexity of the proposed trust model is O ( n ) . Simulations indicate that the proposed trust model can significantly reduce the probability of the errors by the SUBS in the spectrum decision making.